Situation Report: Hungary, 8 March 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. HSWP Still Controls the Arts / by Judith Pataki Police Harassment of Dissidents Intensifies / by Edith Markos Interior Ministry Launches New Attack on Dissidents / by Edith Markos Party Conference Discusses Modern Capitalism / by Judith Pataki Senior Official Admits Differences among Warsaw Pact Members / by Alfred Reisch Yalta and Helsinki Linked as Symbols of Peaceful Coexistence / by Alfred Reisch Comeback for Durable Trade Union Leader? / by Alfred Reisch